(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Ultrasonography is a very useful diagnostic tool for the detection of foetal weight. Objective: The purpose of the present study was to validate the ultrasonography for the detection of foetal weight. Methodology: This prospective cohort study was carried out in the Department of Obstetrics & Gynaecology at Rajshahi Medical Hospital, Rajshahi, Rajshahi, Bangladesh from July 2012 to June 2014 for a period of 2(two) years. Pregnant women with known gestational age at term (38 to 40 weeks of pregnancy), singleton pregnancy with longitudinal lie were included in this study. The patient was then taken to Dept. of Radiology & Imaging, RMCH. Ultrasonographic estimation of foetal weight was done from estimation of foetal abdominal circumference (AC), biparietal diameter (BPD) and foetal femur length (FL). Actual birth weights of babies were measured soon after their birth. The BPD, AC and FL were measured in centimetres and foetal weight was measured in grams. Actual birth weight is the first weight of now-born obtained after birth. This weight was measured within the first hour of life. Result: A total number of 245 pregnant women in term pregnancy were recruited as per inclusion and exclusion criteria. Majority of the women [91(37.1%)] belonged to the age group 19 to 29 years which was 174(71.0%) cases. Low birth weight was found in 12(4.9%) cases ultrasonographic examination and actual low birth weight was found in 15(6.0%) cases. Overweight was found in 13(5.2%) cases ultrasonographic examination and actual birth overweight was found in 9(3.7%) cases. The mean value and SD of foetal weight measured by USG was 2870.41 gms and 424.84 respectively. In case of actual birth weight, the mean and SD was 2936.20 gms and 456.71 respectively (p = 0.05). Conclusion: In conclusion estimation of foetal weight by ultrasonography is not significantly varied. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):16-19